Analisa dan Perancangan Sistem Penyewaan DVD Berbasis Web - Steve Putra; Yakub yakub; Mario Indriawan (ISB Atma Luhur, 2014)
CV. Tarradisc engaged in the DVD rental and has been growing very rapidly from year to year in a rental movie enthusiasts who continue to be updated. Tarradisc penyewaannya intends to computerize the system designed to maximize its performance with this web based rental system. DVD Peenyewaan Information System Web-based on CV Tarradisc consists of several kinds of processes and use the HTML programming language, and PHPMyAdmin database. The purpose of research to design and create rental and reservation system needs a DVD-based movie web where customers can find information neighbor DVD rental prices, the latest film types and registration information. Given this system, expected to mengatasai rental problem manually, can improve the efficiency and effectiveness in firms in taking a decision and able to compete competitively.